The economics of loom weaving industry in Miag-ao, Iloilo - Balindua, Trini Rose .; Fuentespina, Pierra Mapilit (2004.)
The study determined and analyzed the economic profitability of the loom-weaving industry in Miag-ao. Specifically, the study described the socio-demographic profile of owners and laborers, determined the economic profitability, the cost and returns, the contractual arrangement between the owners and laborers and identified the problems encountered in the industry., The primary data were mainly gathered from 5 owners and 2 cooperative chairpersons and 35 weavers who comprised the study population. The respondents came from the different barangays of Banbanan, Bugtong Naulid, Bulucae, Dawog, Guibongan and Indag-an of the town of Miag-ao where loom weaving firms are situated and weavers are concentrated. Employing the cost and return analysis, results showed that loom weaving industry earned positive economic profit. Gross profit amounted to PhP 9,079.83 and financial profit of PhP 8,738.67. The payback period is 4.04 months. Return to the laborer is valued at PhP 5,431.35 and returns to owner is PhP 7,736.46. The problems encountered in the loom waving industry were the cheap compensation of laborers, health problems, old age and poor eye sight, the delay on the provision of materials by the owners to their laborers, lack of buyers during lean season, and the improbability of the return of the finished products by the laborers and the loss of interest of the younger generation in the industry.
Research Paper (Undergraduate, Bachelor of Science in Economics) College of Arts and Sciences,University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Weaving Industry. -- Miag-ao, Iloilo